Breaking the monolith: working through planes of difference - Goel, Kritika; ., . (International Journal of Engineering and Technology, 2018)
The idea of women empowerment is closely associated with the discourse of development. The neoliberal state not only prophesize empowerment as the inevitable route for the women to become developed but also defines this empowerment in its own specific terms. The stateâ€™s version of empowerment that it perpetuates through different institutions is problematic as it essentially push all the women in one direction that is to become a confident, independent, modern subject irrespective of their context, experiences, histories, capabilities. Through my MPhil action research work with the women of a village called Palwadi in Dhamtari district of Chhattisgarh, we are trying to break the homogeneity of empowerment and understand what does empowerment means to us? This paper discusses the rigidity of empowerment which takes women as a homogeneous lot and imposes on them a certain kind of becoming. Next it discusses why is it important to introduce the idea of difference in our understanding as well as methods of engaging with women and women groups. After this, it delves into a possibility of shifting the axis from â€˜who is a womanâ€™ to â€˜what is a womanâ€™ that is from biological woman to woman as embodied, historic, political beings at the same time relating this to the work I have been doing in Palwadi with women Self Help Groups.Â Â